2005
DOI: 10.1007/s10891-005-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Behavior of Mercury Compounds in Coal Combustion Products

Abstract: The main mechanisms of transformation of mercury compounds in coal combustion products in the region of high temperatures have been analyzed. A kinetic model of the process of gas-phase oxidation of metal mercury vapors is proposed. The features of the behavior of the investigated compounds in systems of cleaning combustion products from harmful impurities have been considered.Mercury compounds are among the most toxic and long-lived microimpurities in the atmospheric air. Native sources of mercury emitted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Regardless of the dominant mechanism for mercury oxidation, it is well-known that the transformation from Hg 0 to Hg 2+ in flue gas is kinetically limited. For temperatures below ∼450 °C, at equilibrium, nearly all mercury should exist as Hg 2+ ( , ). Due to the excess of chlorine-containing species (HCl and Cl 2 ), HgCl 2 is assumed to be the dominant form of Hg 2+ .…”
Section: Mercury Oxidation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the dominant mechanism for mercury oxidation, it is well-known that the transformation from Hg 0 to Hg 2+ in flue gas is kinetically limited. For temperatures below ∼450 °C, at equilibrium, nearly all mercury should exist as Hg 2+ ( , ). Due to the excess of chlorine-containing species (HCl and Cl 2 ), HgCl 2 is assumed to be the dominant form of Hg 2+ .…”
Section: Mercury Oxidation Mechanismsmentioning
confidence: 99%
“…As the flue gas cools, some of the Hg 0 is oxidized, presumably to HgCl 2 because of the large excess of chlorine present in coal. The extent of mercury oxidation depends upon a number of factors, including combustion characteristics, coal composition (including chlorine content) ( ), concentrations of other species (i.e., NO x and SO 2 ) ( , ) in the flue gas, and the time−temperature history ( , ). Both Hg 0 and Hg 2+ can enter the particulate phase by adsorption onto fly ash particles ( ).…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, the presence of oxygen is shown to modify this by interacting with the chlorine and reducing the dominance of the dichloride to 1200 K. Such calculations also are very dependent on an accurate and complete database for any species that may be relevant. For example, previous calculations that still incorporate a strong HgO(g) bond strength value based on the JANAF source (268 kJ mol -1 ) (14) or have elements present that have a significant affinity for chlorine or bromine, will erode the thermodynamically expected dominant role for the gaseous dihalides (36)(37)(38). However, as will be seen, this is quite irrelevant and very misleading as the formation in the gas phase of such dihalides is kinetically constrained.…”
Section: Previous Proposed Mechanismsmentioning
confidence: 99%
“…Industrial research results confirm that mercury emission to the atmosphere depend on several factors (Hall et al, 1991;Galbreath & Zygarlicke, 2000;Gerasimov, 2005;Zhang et al, 2008). These include: mercury content and chemical composition of combusted coal, type of boiler, mercury speciation of flue gases leaving boiler, types and efficiency of exhaust gas purification processes and presence of specified components in fly ashes and flue gases.…”
Section: Introductionmentioning
confidence: 89%